WOLFF, F. Socrate. Paris: PUF, 1985. (Phibsophies). 128 p. - Novak, Maria da Glória (Classica - Revista Brasileira de Estudos Clássicos, 1989)
WOLFF, F. Socrate. Paris: PUF, 1985. (Phibsophies). 128 p.